2024
DOI: 10.1088/2632-2153/ad1f77
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of generative adversarial nets (GANs): a survey of the state-of-the-art

Tanujit Chakraborty,
Ujjwal Reddy K S,
Shraddha M Naik
et al.

Abstract: Generative Adversarial Networks (GANs) have rapidly emerged as powerful tools for generating realistic and diverse data across various domains, including computer vision and other applied areas, since their inception in 2014. Consisting of a discriminative network and a generative network engaged in a Minimax game, GANs have revolutionized the field of generative modeling. In February 2018, GAN secured the leading spot on the ``Top Ten Global Breakthrough Technologies List'' issued by the Massachusetts Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 204 publications
(280 reference statements)
0
1
0
Order By: Relevance
“…After evaluating KID metric (Table 3), it is evident that 1400 epochs are insufficient for both models to generate images of adequate quality, and the improvement in quality stops with continued training. It is hypothesized that such results are achieved due to limited dataset as several studies have found the CGAN and DCGAN models to excel with large-scale datasets such as ImageNet (Chakraborty et al, 2024). In such cases, the application of transfer learning technique, specifically fine-tuning, could be considered.…”
Section: Cgan and Dcgan Network Experimental Resultsmentioning
confidence: 99%
“…After evaluating KID metric (Table 3), it is evident that 1400 epochs are insufficient for both models to generate images of adequate quality, and the improvement in quality stops with continued training. It is hypothesized that such results are achieved due to limited dataset as several studies have found the CGAN and DCGAN models to excel with large-scale datasets such as ImageNet (Chakraborty et al, 2024). In such cases, the application of transfer learning technique, specifically fine-tuning, could be considered.…”
Section: Cgan and Dcgan Network Experimental Resultsmentioning
confidence: 99%